Disc degeneration influences the strain magnitude and stress distribution within the adjacent trabecular bone - Raftery, Kay A.; Kargarzadeh, Alireza; Tavana, Saman; Newell, Nicolas (Frontiers in Bioengineering and Biotechnology, 2024)
IntroductionUp to one in five will suffer from osteoporotic vertebral fracture within their lifetime. Accurate fracture prediction poses challenges using bone mineral density (BMD) measures. Trabecular bone strains may be influenced by the underlying intervertebral disc (IVD). Understanding how disc degeneration alters load distribution to the vertebra may demonstrate that supplementing fracture risk tools with IVD metrics could improve predictions. The aim of this study was to assess the influence of IVD degeneration on the stress and strain magnitude and distribution in the trabecular bone of adjacent vertebrae.MethodsTen human cadaveric lumbar bi-segment specimens (20 IVDs, 9 degenerated, 11 non-degenerated) were µCT-imaged under 1000N. Digital volume correlation was used to quantify axial, principal, maximum shear, and von Mises strain in the superior and inferior regions of the vertebra. Volumetric BMD from quantitative-CT was used to calculate Young’s modulus, which was then registered with the von Mises strain field to calculate internal von Mises stress.ResultsTwo bi-segments fractured during mechanical testing, resulting in N = 8 endplate regions per group. Trabecular bone adjacent to degenerated IVDs presented higher maximum principal and shear strains in the anterior region, relative to non-degenerated (peak ε1: 6,020 ± 1,633 µε versus 3,737 ± 1,548 µε, p < 0.01; peak γmax: 6,202 ± 1948 µε versus 3,938 ± 2086 µε, p < 0.01). Von Mises stress distribution was significantly skewed towards the anterior region in the degenerated group only (28.3% ± 10.4%, p < 0.05). Reduced disc height correlated with increased central-region axial compressive strain, decreased central-region BMD, and increased anterior region von Mises stress (all p < 0.05).DiscussionDisc degeneration may encourage high strains to be experienced within the anterior region of the adjacent bone, owing to changes in load distribution. This study demonstrates the potential of utilising IVD metrics in fracture risk assessment, to inform clinical decision making and preventative treatment.